Training and Empowerment of Marunda Coastal Communities regarding Introduction to Types and Planting of Mangroves in North Jakarta - Hamzah, A. Hadian Pratama; Nurhasanah, Nurhasanah; Nurul, Ruti; Effendi, Hermanto Ray (LP2M INSURI Ponorogo, 2024)
Changes in coastal land use can affect the condition of coastal ecosystems, including mangrove ecosystems which are typical vegetation in coastal areas. Mangrove ecosystems are only left in certain highly protected areas or planted on the edge of ponds bordering beaches or rivers to prevent abrasion. The thinning of mangrove forests in the coastal area of ​​Marunda, North Jakarta makes it easy for sea water to enter residential areas. The reduction in mangrove land in the coastal area of ​​North Jakarta has an impact on decreasing the environmental quality of the coastal area. This environmental community service activity aims to encourage awareness of the coastal environment which must be pursued by all levels of society, including the academic community, especially students and lecturers. The method for implementing this activity is collaboration and participation of local communities that the community around Marunda is involved in environmental conservation activities through the introduction of mangrove planting. Their introduction to the environment and its preservation can start from efforts to repair environmental damage itself. This service activity is an example of real implementation to overcome this problem. As a result of this activity, the community can introduce the types of mangrove plants as well as provide public learning for each generation regarding involvement in preserving the coastal environment for each future generation to take a role in protecting the environment and saving generations from ecological disasters in the future.